2018
DOI: 10.1371/journal.pone.0206009
|View full text |Cite
|
Sign up to set email alerts
|

Effect of adherence to growth hormone treatment on 0–2 year catch-up growth in children with growth hormone deficiency

Abstract: BackgroundQuantifying the association between adherence and the growth response to growth hormone (GH) treatment is hampered by suboptimal methods of measuring adherence, confounders associated with the growth response, and restriction of the outcome parameters to yearly growth velocities.AimTo investigate the effect of adherence on the two-year growth response to GH treatment in prepubertal children with idiopathic isolated growth hormone deficiency (GHD) participating in the easypod connect observational stu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
60
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 56 publications
(66 citation statements)
references
References 31 publications
4
60
2
Order By: Relevance
“…The global ECOS study found a positive correlation between adherence and attainment of growth milestones [6]. Contrary to previous reports [5,13], here, we found a significant correlation between adherence and growth outcomes at 1-year after initiating r-hGH therapy with Easypod™. This difference among ECOS subpopulations may be due to sample size differences as well as the proportions of r-hGH therapy indications, which may lead to potential differences in the magnitude of clinical response.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…The global ECOS study found a positive correlation between adherence and attainment of growth milestones [6]. Contrary to previous reports [5,13], here, we found a significant correlation between adherence and growth outcomes at 1-year after initiating r-hGH therapy with Easypod™. This difference among ECOS subpopulations may be due to sample size differences as well as the proportions of r-hGH therapy indications, which may lead to potential differences in the magnitude of clinical response.…”
Section: Discussioncontrasting
confidence: 99%
“…The human recombinant growth hormone (h-rGH) is indicated to treat clinical conditions that imply short stature, such as GH deficiency (GHD), children born small for gestational age (SGA) who failed to show catch-up growth and Turner syndrome (TS), among other medical conditions [1][2][3][4][5][6]. Adherence to h-rGH is one of the most important factors that determine achievement of clinical targets [7−10].…”
Section: Introductionmentioning
confidence: 99%
“…Its application to the treatment of growth disorders is more challenging because therapy is geared to long-term responses and benefits, rather than short-term metabolic control. However, one area where digital technology has been effective is in the electronic monitoring of GH injections ( 13 , 14 ). The use of an electromechanical auto-injector, which records every injection that is given and communicates the data both to the patient and the HCP, is a major advance ( 15 ).…”
Section: Digital Advances In the Management Of Growth Disordersmentioning
confidence: 99%
“…The difference between observed and predicted gain in height or height velocity can be a measure of the adherence to the hGH treatment regimen. If responsive reduced while the diagnosis is correct and the presence of intercurrent disease is ruled out, poor adherence to the hGH regimen should be considered [45,46]. Monitoring of adherence should begin as the hGH treatment is initiated because some patients may not be compliant from the start or not renew their prescriptions, particularly if the evidence of real benefit is lacking [47][48][49].…”
Section: Poor Adherence To Rhgh Therapymentioning
confidence: 99%
“…Electronic monitoring of GH injections can be performed using the easypod injection device and Easypod Connect system, which is the only such device currently approved [45]. The device facilitates administration of a preset dose of hGH, records injection times and doses, and provides the patient with information such as number of doses remaining [53].…”
Section: Poor Adherence To Rhgh Therapymentioning
confidence: 99%